AIDS incidence and mortality in injecting drug users: the AjUDE-Brasil II Project - Cardoso Mauro Nogueira; Caiaffa Waleska Teixeira; Mingoti Sueli Aparecida (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
This paper presents AIDS incidence and mortality among injecting drug users (IDUs) reached by the AjUDE-Brasil II Project. From a cross-sectional survey, 478 IDUs were interviewed in three Brazilian cities: Porto Alegre, São José do Rio Preto, and Itajaí. The cohort was followed up in the Brazilian surveillance database for AIDS and mortality during 2000 and 2001. AIDS incidence was 1.1 cases per 100 person-years, and the mortality rate was 2.8 deaths per 100 person-years. AIDS cases only occurred in IDUs who reported ever having shared injecting equipment. Female gender (RR = 5.30), homelessness (RR = 6.16), and report of previous sexual relations with same-sex partners (RR = 6.21) were associated with AIDS. Deaths occurred only among males. Homelessness (RR = 3.00), lack of income (RR = 2.65), HIV seropositive status (RR = 4.52), and no history of incarceration (RR = 3.71) were also associated with death. These findings support evidence that gender and socioeconomic conditions are both determinants of morbidity and mortality in Brazilian IDUs.